HUBUNGAN FAKTOR RISIKO DENGAN TIPE HISTOPATOLOGI KANKER ENDOMETRIUM DI BEBERAPA RUMAH SAKIT KOTA MEDAN TAHUN 2015 – 2018 - NAHDIANA RIZQI RAHMAINI; SITI MIRHALINA (LP2MTBM MAKARIOZ, 2021)
Endometrial cancer is gynecological cancer. Endometrial cancer is classified into type I and type II. Several factors havebeen linked to an increased risk of endometrial cancer. The relationship between age, parity, history of hypertension, obesity,age of menarche, and a history of infertility for endometrial cancer are controversial from several studies. This researchmethod is an analytic observational study with a cross-sectional study. Research subjects were 31 cases of endometrialcancer diagnosed and registered in Dr Pirngadi Medan Hospital and Medan Haji Hospital in 2015-2018 that met the inclusionand exclusion criteria. The sampling technique uses total sampling. There are effects of age, parity, duration of use ofhormonal contraception, history of diabetes, history of hypertension, obesity, age of menarche and history of infertility withhistopathological type of endometrial cancer. All variables have the same strong relationship with the histopathological typeof endometrial cancer.